2022
DOI: 10.1111/jen.13081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet switching from almond pollen to natural prey on predation capacity of Neoseiulus cucumeris

Abstract: Monitoring the performance of a predator long-term reared on a non-prey diet when switches to a prey is extremely important to have a successful biological control program. In the current study, the efficacy of Neoseiulus cucumeris Oudemans long-term reared on almond pollen during 30 generations in encountering with its natural prey, Tetranychus urticae Koch was evaluated under laboratory conditions. Every 10 generations (G1, G10, G20 and G30), the development, reproduction, population growth potential and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…putrescentiae, was 0.278. N. bicaudus experienced a decline in its intrinsic rate of increase upon prey switching, similar to the observed decrease also seen in N. cucumeris' intrinsic rate of increase following prey switching [43]. The intrinsic rate of increase serves as a crucial parameter for evaluating and comparing pest population dynamics; it is also influenced by mortality and developmental duration factors [44].…”
Section: Discussionsupporting
confidence: 56%
“…putrescentiae, was 0.278. N. bicaudus experienced a decline in its intrinsic rate of increase upon prey switching, similar to the observed decrease also seen in N. cucumeris' intrinsic rate of increase following prey switching [43]. The intrinsic rate of increase serves as a crucial parameter for evaluating and comparing pest population dynamics; it is also influenced by mortality and developmental duration factors [44].…”
Section: Discussionsupporting
confidence: 56%
“…Switching N. cucumeris mites from saffron pollen to natural prey (T. urticae) after 10 and 20 generations showed that the values of the population growth parameters such as GRR, R 0 , and r did not decrease over the generations; N. cucumeris after 10 and 20 generations on almond pollen (Yazdanpanah et al 2023) and cattail pollen (Gravandian et al 2022) had similar results. However, when N. cucumeris fed on the natural prey, T. urticae, the total lifespan decreased significantly; mostly because of decreasing in adult longevity.…”
Section: Generationmentioning
confidence: 77%
“…Our study revealed that saffron pollen did not affect negatively the predation capacity of N. cucumeris after 20 generations. Similarly, N. cucumeris maintained its predation potential after 20 generations of rearing on cattail pollen (Gravandian et al 2022), and after 30 generations of feeding on almond pollen (Yazdanpanah et al 2023).…”
Section: Generationmentioning
confidence: 89%
“…Monitoring the performance of a predator long-term reared on a non-prey diet when switching to its prey is extremely important to have a successful biological control program (Yazdanpanah et al . 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the performance of a predator long-term reared on a non-prey diet when switching to its prey is extremely important to have a successful biological control program (Yazdanpanah et al 2023). Because of the high performance of A. swirskii when fed with the bird-of-paradise pollen, the predation potential of the predator was evaluated during the rearing process when switched to the natural prey, T. urticae.…”
Section: Discussionmentioning
confidence: 99%